2015
DOI: 10.1002/2014gl062943
|View full text |Cite
|
Sign up to set email alerts
|

Red and far red Sun‐induced chlorophyll fluorescence as a measure of plant photosynthesis

Abstract: Remote estimation of Sun-induced chlorophyll fluorescence emitted by terrestrial vegetation can provide an unparalleled opportunity to track spatiotemporal variations of photosynthetic efficiency. Here we provide the first direct experimental evidence that the two peaks of the chlorophyll fluorescence spectrum can be accurately mapped from high-resolution radiance spectra and that the signal is linked to variations in actual photosynthetic efficiency. Red and far red fluorescence measured using a novel airborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
141
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 35 publications
9
141
0
Order By: Relevance
“…The residual error is lower than a few-tenths of mW m −2 sr −1 nm −1 , and it is probably caused either by slight changes of the reference irradiance spectrum or errors introduced from the 3FLD method. The SIF values retrieved for vegetated targets are higher and fall in the range of values obtained by field spectroscopy measurements reported in the literature [9,[48][49][50]65,72,73]. The obtained results strongly agree with the findings of Rossini et al [73].…”
Section: Radiance Hyuas Reflectancesupporting
confidence: 90%
See 1 more Smart Citation
“…The residual error is lower than a few-tenths of mW m −2 sr −1 nm −1 , and it is probably caused either by slight changes of the reference irradiance spectrum or errors introduced from the 3FLD method. The SIF values retrieved for vegetated targets are higher and fall in the range of values obtained by field spectroscopy measurements reported in the literature [9,[48][49][50]65,72,73]. The obtained results strongly agree with the findings of Rossini et al [73].…”
Section: Radiance Hyuas Reflectancesupporting
confidence: 90%
“…In particular, our results are strongly in agreement with general statements drawn in the conclusions of their work: (i) SIF values are in the range of 0 to 3 mW m −2 sr −1 nm −1 ; (ii) the highest values were measured on crops and meadow followed by broadleaf plants; (iii) the absolute values and uncertainties are very similar, even though the differences in plant species prevent a direct quantitative comparison. Although SIF is a highly dynamic signal, the comparison of our results with those reported in [73] is motivated by the fact that in both cases, spectral measurements were collected around noon during typical clear-sky days in summer at mid-latitudes. In these conditions, the illumination can be considered almost comparable, at least within a short timeframe around noon.…”
Section: Radiance Hyuas Reflectancementioning
confidence: 86%
“…It has been shown that relative magnitude of the red and far‐red fluorescence is sensitive to nitrogen uptake, chlorophyll content, and responses to stress conditions such as low temperature (Agati et al, 1995, 1996; Campbell, Carmichael, & Chai, 2008; Campbell, Middleton, et al, 2008; Campbell et al, 2007; Corp et al, 2003; Rossini et al, 2015). Most of the studies using SIF, including ours, to estimate terrestrial GPP have so far focused on using the far‐red SIF emission.…”
Section: Discussionmentioning
confidence: 99%
“…However, the spectral resolution of the CASI sensor is not optimal for the estimation of F760 and we cannot exclude that the lower performances of F760 in stress detection compared to Tc could be partially explained by F760 estimations not accurate enough. A new airborne sensor specifically intended for sun-induced chlorophyll fluorescence estimation has been recently developed by the Forschungszentrum Jülich (Germany) in cooperation with the Finnish company Specim [44] and will open the possibility to fully verify the potential of fluorescence for stress detection with the best currently available spectral and radiometric resolution in the red and far-red regions.…”
Section: Diurnal Variations Of Optical Indices and Fluorescencementioning
confidence: 99%